Społeczność polska w Wielkiej Brytanii w świetle współczesnej twórczości powieściowej. Analiza mimetyczna - Romejko, Adam (Polityka i Społeczeństwo, 2021)
René Girard’s mimetic theory is based on an analysis of a variety of literary works, including novels, myths and the Bible. Its main assumption is that human behaviour is animated by mimesis. Under certain conditions it can lead to serious conflicts. In the past, communities coped with this problem using a system based on the mechanism of victimization (the scapegoat ritual). The Girardian insights may be applied in studies focusing on the Polish community in the United Kingdom, especially by analyzing literary works. Research can reveal an image that is different from the ones that are often promoted. The Poles who settled in Great Britain were and still are average people and not heroes whom they consider themselves to be. On the British soil they look for per-sonal happiness and want a normal life among those who accept and love them.